2012
DOI: 10.1161/circulationaha.111.064030
|View full text |Cite|
|
Sign up to set email alerts
|

Endothelial Cell–Specific FGD5 Involvement in Vascular Pruning Defines Neovessel Fate in Mice

Abstract: Background-New vessel formation contributes to organ development during embryogenesis and tissue repair in response to mechanical damage, inflammation, and ischemia in adult organisms. Early angiogenesis includes formation of an excessive primitive network that needs to be reorganized into a secondary vascular network with higher hierarchical structure. Vascular pruning, the removal of aberrant neovessels by apoptosis, is a vital step in this process. Although multiple molecular pathways for early angiogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 27 publications
(27 reference statements)
5
67
3
Order By: Relevance
“…We found that EC apoptosis was predominantly located in regressing vessels during angiogenesis and several studies have previously shown that levels of EC apoptosis during retina angiogenesis directly correlate with levels of vessel regression (Cheng et al, 2012;Korn et al, 2014;Savant et al, 2015;Simonavicius et al, 2012). Despite this, our genetic approach of inactivating EC apoptosis shows that it is not causative of vessel regression, consistent with recent findings that only 5% of regressing vessels in the retina contain apoptotic ECs (Franco et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that EC apoptosis was predominantly located in regressing vessels during angiogenesis and several studies have previously shown that levels of EC apoptosis during retina angiogenesis directly correlate with levels of vessel regression (Cheng et al, 2012;Korn et al, 2014;Savant et al, 2015;Simonavicius et al, 2012). Despite this, our genetic approach of inactivating EC apoptosis shows that it is not causative of vessel regression, consistent with recent findings that only 5% of regressing vessels in the retina contain apoptotic ECs (Franco et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Apoptosis is well-documented in retina angiogenesis, but reports differ as to its correlation with vessel pruning (Cheng et al, 2012;Hughes and Chan-Ling, 2000;Korn et al, 2014;Savant et al, 2015;Simonavicius et al, 2012), with as few as 5% of pruned vessels containing apoptotic ECs (Franco et al, 2015). Furthermore, apoptosis is rarely observed during vessel regression in zebrafish (Chen et al, 2012;Kochhan et al, 2013;Lenard et al, 2015), and is largely dispensable for the regression of those vessels in which it does occur (Kochhan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of mice with the non-canonical Wnt signaling inhibitor TNP470 phenocopied the reduced proliferation and increased Cdkn1a expression of Evi-ECKO mice, which is an important negative regulator of cell cycle progression (Zhang et al, 2000;Gartel et al, 2001;Cirone et al, 2008). Similar to the Evi-ECKO phenotype, Fgd5-dependent vessel regression correlated with increased Cdkn1a expression, subsequent cell cycle arrest and apoptosis, arguing for an important role of Cdkn1a in regulating vessel regression by interfering with EC proliferation and survival (Cheng et al, 2012). In our study, TNP470 treatment inhibited EC proliferation by promoting Cdkn1a upregulation, but did not affect EC apoptosis, correlating with unchanged Tek, Stat2 and Bax expression.…”
Section: Discussionmentioning
confidence: 89%
“…For instance, depletion of vascular endothelial growth factor (VEGF) after primary network formation induced vessel regression correlating with detachment and increased apoptosis of ECs (Alon et al, 1995;Baffert et al, 2006). Furthermore, leukocytes promote pruning of retinal vessels by inducing EC apoptosis and FGD5/Cdkn1a/p53 signaling interferes with EC survival, stimulating subsequent vessel regression (Ishida et al, 2003;Cheng et al, 2012). However, whether vessel regression is initially triggered by apoptosis due to withdrawal of survival factors or whether regression is followed by apoptosis of retracted ECs that have lost cell-cell and cell-matrix contact remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Like EXC-5 in EC tubulogenesis, members of the mammalian FGD family have been implicated in various tubulogenic processes, such as vascular development (Cheng et al, 2012;Daubon et al, 2011;Kurogane et al, 2012). Moreover, recessive loss-of-function mutations in FGD4 underlie a CMT neuropathy that exhibits cellular phenotypes similar to those caused by dominant gain-offunction mutations in INF2 (De Sandre-Giovannoli et al, 2005;Delague et al, 2007;Fabrizi et al, 2009;Mathis et al, 2014).…”
Section: Potential Implications For Human Diseasementioning
confidence: 99%